Checklist of the parasites of the Black-necked Swan, Cygnus melanocoryphus (Aves: Anatidae), with new records from Chile - González Acuña, Daniel (2010)
Black-necked swans (Cygnus melanocoryphus) are endemic to the southern cone of South America. Their range extends from Brazil and Paraguay south to Argentina and Chile. A total of 16 parasite species were collected from 7 swans from the Biobío region, Chile, of which 12 are new records for Chile and 11 represent new host records, Echinostoma trivolvis, Paranomostomum sp., Microsomacanthus sp., Nadejdolepis sp., Retinometra sp., Avioserpens sp., Capillaria skrjabini, Ingrassia cygni, Anatoecus penicillatus, A. icterodes and A. keymeri. A checklist is presented that summarizes sites of infections, localities, life cycles and their intermediate hosts (if known), and the pertinent references to demonstrate the wide diversity of parasites of black-necked swans. Our review of the existing literature (23 publications) along with our own records provided information on a total of 18 families and 27 genera, including 33 described species (some only identified to genus), of which 11 were recorded only in Chile (8 endoparasites and 3 ectoparasites), and 6 only in Argentina (4 endoparasites and 2 ectoparasites). Five parasites are known only from captive swans in European zoos. Parasites recorded from C. melanocoryphus include 23 helminths and 10 ectoparasites (one leech and 9 arthropods).